1997
DOI: 10.1016/s0741-5214(97)70326-4
|View full text |Cite
|
Sign up to set email alerts
|

Alternative approach for management of infected aortic grafts

Abstract: In-line aortic bypass for treatment of aortic graft infections yields excellent results and has become our treatment of choice in dealing with this difficult problem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 11 publications
0
21
0
Order By: Relevance
“…In our series, this was actually identified in cases 1 and 2, but was not identified in case 8. The results of partial graft removal in the previous reports are as follows: perioperative mortality, 0%-13%; major amputation, 0%-13% 14,24,47,49 (Table 4B). …”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In our series, this was actually identified in cases 1 and 2, but was not identified in case 8. The results of partial graft removal in the previous reports are as follows: perioperative mortality, 0%-13%; major amputation, 0%-13% 14,24,47,49 (Table 4B). …”
Section: Discussionmentioning
confidence: 90%
“…No stump blowout occurred in any patient. Beside the axillary artery as an inflow source after aortic graft excision, the descending thoracic aorta or noninfected proximal aorta (in-line technique) 23,24 has been also used. The follow-up results of 16 patients using the in-line technique by Darling et al 24 were as follows: perioperative mortality, 0%; major amputation, 0%; new graft infection, 0%; new graft failure 25%; aortic stump blowout, 8%.…”
Section: Discussionmentioning
confidence: 99%
“…Infection can also develop after percutaneous stent angioplasty but in low rates (0.5%). [14,15] Early graft infections usually affect extracavitary grafts, while majority of late infections involve cavitary (i.e., aortic) grafts. [16] …”
Section: Epidemiologymentioning
confidence: 99%
“…Alternative therapies include partial or total graft excision, in situ prosthetic replacement after debridement, or in situ allograft replacement. 11,12 All of these techniques have mortality rates ranging from 30% to 70% and extensive morbidity, with amputation rates approaching 30%. [13][14][15][16][17] In studies that reported results of extra-anatomic bypass for abdominal aortic graft infection, the overall patency is ϳ65% at 3 years.…”
Section: Betweenmentioning
confidence: 99%
“…14 It has been shown that in situ bypass grafts for severe aortic graft infection were followed by 100% reinfection and 38% mortality rates. Some authors 12,23,24 have noted a high rate of suture line breakdown, patch rupture, and bleeding when new autologous tissue patches or grafts are placed in an infected field. On the other hand, Farkas et al 25 have observed that positive cultures of benign aneurysms are not related to increased risk of secondary graft sepsis.…”
Section: Betweenmentioning
confidence: 99%